Effects of Expressive Writing on Neural Processing During Learning - DiMenichi, Brynne C.; Ceceli, Ahmet O.; Bhanji, Jamil P.; Tricomi, Elizabeth (Frontiers in Human Neuroscience, 2019)
Expressive writing about past negative events has been shown to lead to a slew of positive outcomes. However, little is known about why writing about something negative would have positive effects. While some have posited that telling a narrative of a past negative event or current anxiety “frees up” cognitive resources, allowing individuals to focus more on the task at hand, there is little neural evidence that expressive writing has an effect on cognitive load. Moreover, little is known about how individual differences in the content of expressive writing could affect neural processing and the cognitive benefits writing confers. In our experiment, we compared brain activity in a group that had engaged in expressive writing versus a control group, during performance on a feedback-based paired associate word learning task. We found that across groups, differential activation in the dorsal striatum in response to positive versus negative feedback significantly predicted better later memory. Moreover, writing about a past failure resulted in more activation relative to the control group during the learning task in the mid-cingulate cortex, an area of the brain crucial to processing negative emotion. While our results do not provide support for the assertion that expressive writing alters attentional processing, our findings suggest that choosing to write about particularly intense past negative experiences like a difficult past failure may have resulted in changes in activation in areas of the brain typically associated with emotional processing, resulting in greater cognitive and emotional benefits.